Effect of bio activators’ application and manual fruit thinning on yield and quality of melon (Cucumis melo L.) grown under protected cultivation in Costa Rica - Alvarado-Sánchez, Tania (2015)
The effects of manual fruit thinning and of applying the bio activators Algamix and Engordone on the yield and quality of yellow honey dew melon var. JMX-902, were evaluated. Significant differences were not found with respect to fruit firmness, total soluble solids concentration, fruit weight, total yield, marketable fruit weight, marketable yield, and yield per plant. Significant differences between treatments were found for the number of fruits per plant: Plants treated with Engordone alone and Algamix alone showed higher number of fruits per plant compared to other treatments, but these results were not different from the Control. Significant differences were also observed by distributing the output per weight categories: With respect to the other treatments, the yield of melon fruits weighting between 601-800 grams was higher in plants treated with Algamix alone, and the yield of melon fruits weighting between 801-1000 grams was higher in plants treated with Engordone alone.